Currency regime crises, real wages, functional income distribution and production - Emiliano Brancaccio; Nadia Garbellini (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
This study examines 28 selected cases of transition from a fixed to a more flexible exchange rate combined with devaluation over the period 1980–2013. The crises examined generally prove to be significantly correlated to a reduction in real wages and the wage share. However, both groups are also characterised by an important degree of variability with respect to sample averages, which suggests that the dynamics of real wages and wage shares were also influenced by the specific institutional and political environments in which such crises and devaluations took place. Finally, there appear to be no adequate empirical grounds for the claim that a decrease in real wages resulting from a currency regime crisis will result in improved levels of production and employment. All evaluations of the links between the currency regime and the dynamics of wages and distribution should in any case be carried out not in abstract terms but by comparing the possible implications of abandoning the regime with those of maintaining it. The opportunity of a comparative analysis also applies to the study of current episodes, such as the eurozone crisis.
Keywords: E24; E25; F30; F40; 330; currency regime crisis; euro; real wages; wage share